2014
DOI: 10.3109/09273948.2014.986581
|View full text |Cite
|
Sign up to set email alerts
|

Age-related Defects in Ocular and Nasal Mucosal Immune System and the Immunopathology of Dry Eye Disease

Abstract: Dry eye disease (DED) is a prevalent public health concern that affects up to 30% of adults and is particularly chronic and severe in the elderly. Two interconnected mechanisms cause DED: (1) an age-related dysfunction of lacrimal and meibomian glands, which leads to decreased tear production and/or an increase in tear evaporation; and (2) an age-related uncontrolled inflammation of the surface of the eye triggered by yet-to-be-determined internal immunopathological mechanisms, independent of tear deficiency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 243 publications
(245 reference statements)
0
5
0
Order By: Relevance
“…Therefore, in recent years, a large number of basic and applied researches have been conducted to further investigate the sex differences. Women were found to have distinctly higher incidence and degree of severity of dry eye, [ 3 , 15 ] and the reduction in estrogen is related to the occurrence of dry eye. [ 16 , 17 ] Sex-based differences exist in the lacrimal glands and Moll glands in terms of anatomy, physiology, and pathophysiology, and this kind of difference is also reflected in conjunctival goblet cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in recent years, a large number of basic and applied researches have been conducted to further investigate the sex differences. Women were found to have distinctly higher incidence and degree of severity of dry eye, [ 3 , 15 ] and the reduction in estrogen is related to the occurrence of dry eye. [ 16 , 17 ] Sex-based differences exist in the lacrimal glands and Moll glands in terms of anatomy, physiology, and pathophysiology, and this kind of difference is also reflected in conjunctival goblet cells.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] According to the current epidemiological studies, the incidence of dry eye in China reached up to about 21% to 30%, which was similar to that in other Asian countries and higher than that in the United States and Europe. [ 2 , 3 ] Many factors, including ocular surgery, could induce or aggravate symptoms of dry eye. In recent years, phacoemulsification with intraocular lens implantation has been the main surgical treatment for cataract.…”
Section: Introductionmentioning
confidence: 99%
“…We think that the TED MGD might be seborrheic MGD [40], with excessive secretion of cloudy meibomian lipids. Moreover, the inflammation of eye contents also affects the meibomian gland and the poor secretion quality of the meibum [41]. Lagophthalmos is incomplete eyelid closure, which results in exposure keratitis [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…As such, more promising DED agents are those directed towards reducing inflammation and restoring normal tear film though currently there is no specific immunotherapy for DED [29]. A 2017 review of cyclosporin A (CsA) for the treatment of chronic dry eye [30] indicated strong evidence of efficacy in treating signs but not symptoms.…”
Section: Dry Eye Disease As An Inflammatory Disordermentioning
confidence: 99%